“Study of low birth weight babies and their association with maternal risk factors.” - Dr. M. Sarika; Dr. Rashmi Vishwakarma; Dr. Rajasekhar Rao (Pediatric Review: International Journal of Pediatric Research, 2020)
Objective: To study the prevalence of low birth weight babies and to find their association with maternal risk factors. Methods: This is a hospital-based prospective, observational, conducted in Kamineni Hospital, LB Nagar, Hyderabad. Data about maternal exposure to different risk factors were recorded using a preformed questionnaire. The information included the socio-demographic profile of the mother and her family, obstetric history of the mother especially about previous births, abortions, pre-pregnancy weight, height, weight gain during pregnancy, antenatal services obtained by the mother. Results: Out of 286 newborns 77 newborns were of low birth weight i.e., the prevalence of low birth weight in my study was 26.9% Prevalence of low birth weight was more in female babies, mothers from rural areas, illiterate mothers(40.54), more in mothers who had pregnancy-induced hypertension(54.28), more in multigravida mothers, more in mothers who had irregular antenatal check-ups (45.65%) more in mothers who gained less than 6kgs during pregnancy, more in mothers who had oligohydramnios (50%). Conclusion: This study shows that bio-demographic and prenatal care variables have the strongest influence in determining the birth weight of a baby. However, Socio-economic and demographic factors are significantly associated with prenatal care, which is one of the behavioral factors associated with low birth weight.